AGENDA SETTING HARIAN TRIBUN BATAM DALAM PEMBERITAAN IMPLEMENTASI KAWASAN EKONOMI KHUSUS: Ageng Rara Cindoswari, Sholihul Abidin, Hendri Herman - Jurnal COMMED (Prodi Ilmu Komunikasi Universitas Putera Batam, 2017)
The agenda of setting media is the media directing the public what is the main issue and perceived by thepublic as the main issue. The agenda setting concept recognizes three agendas, namely the media agenda,the public agenda, and the policy agenda. Type This research is descriptive research with quantitativeapproach and survey method. Location and object of research is selected purposively (deliberately) wherethe City of Batam is a city given the privilege of the status of the region that is Special Economic Zone(KEK). The sample was 399 people determined by cluster random sampling. The research was conducted byspreading the questionnaire and analyzed by Rank Spearman correlation. The result of this research showsthat 63,4% of SEZ implementation report in Batam Tribun Daily has high media agenda, 74,2% containshigh enough public agenda.